A Kierkegaardian analysis of Emily Brontë’s Heathcliff and Najib Mahfouz’s Saeed Mehran - Alhiyari, Ibrahim; Zuraikat, Malek J; Omet, Aida (Research Journal in Advanced Humanities, 2026)
The male antiheroes in Emily Brontë’s Wuthering Heights (WH) and Najib Mahfouz’s Al-liṣ wal-Kilāb (AK) offer a relevant example for the dilemma of living in alignment with the Kierkegaardian concept of “anxiety” (or angst) and its “absurd” and “nihilistic” derivatives. One overarching demerit of Heathcliff’s and Saeed Mehran’s existential dilemmas is their sinful, “hereditary” legacy which consistently throttles their freedom of choice and prompts them to develop their own ethics while undertaking a “leap of faith”. Their angst journeys while testing their societies’ permissibility is beset with melancholy which progressively alters into an attritional, nihilistic existence. The two men share many elements such as being betrayed by their women, partaking in Kierkegaard’s “beyond-faith” shift, experiencing 3-4-year estrangement hiatuses at the end of which they return dramatically changed, undergoing Gothic, graveyard setting, having no normative family units, and being prepossessed by an uncommonly poignant, revenge motif.